Comparison of enamel color alteration between bonded and free unbonded surfaces of maxillary anterior teeth after fixed orthodontic therapy (A prospective clinical study) - Yasir R Al-Laban (College of Dentistry/ University of Baghdad, 2015)
Background: The purpose of this study is to compare the color changes between the bonded middle third and the unbonded gingival and incisal thirds, fallowing fixed orthodontic treatment Material and method: The color parameter l, a, b has been recorded for each thirds in upper anterior teeth by mean of easy shad device. The has been calculated for gingival, middle and incisal thirds for the upper anterior teeth in 34 patient, 17 males and 17femals, those subject undergone fixed orthodontic treatment Results: The in middle bonded third is highly significant higher than that in incise and gingival thirds p